THE ANALYSIS OF COMMUNICATION AND COLLABORATION SKILLS IMPROVEMENT OF JUNIOR HIGH SCHOOL STUDENTS USING MULTIMEDIA-BASED INTEGRATED INSTRUCTION IN LEARNING REFLECTION CONCEPT - Kaniawati, Ida (Jurnal Pengajaran MIPA, 2018)
The purpose of this study is to identify the communication and collaboration skills improvement of junior high school studentsin learning science using Integrated Multimedia-Based Instruction (MBI2). This computer multmedia has been designed by researchers and it focuses on the reflection concept. The research subjects are 31 eighth-grade junior high school students who used this multimedia during four meetings learning. The method used is pre-experimental research withone-shot casestudy design. The results show that the students' communication and collaboration skills increases, shown by the average score of each meeting increases and the change in the low category into the good category. In conclusion, the use of MBI2in science learning materials particularly in the reflection concept can improve the communication and collaboration skills of junior high school students.